Technological Development and the Boundaries of the Firm: A Knowledge-Based Examination in Semiconductor Manufacturing - Macher, Jeffrey T. (Management Science, 2006)
This paper examines how the knowledge-based view (KBV) can be applied to firm boundary decisions and the performance implications of those decisions. At the center of the paper is a theoretical and empirical examination of how firms most efficiently organize to solve different types of problems related to technological development, using the semiconductor industry as the empirical setting. Measures that capture important dimensions of performance support the proposition that organization affects performance in problem solving related to knowledge development. Integrated firms realize performance advantages when problem solving in technological development is ill structured and complex, while the same is true for specialized firms when problem solving in technological development is well structured and simple. Performance differences also arise from the presence of scale economies and scope economies.